2019
DOI: 10.1177/2059204319861719
|View full text |Cite
|
Sign up to set email alerts
|

An Agenda for Best Practice Research on Group Singing, Health, and Well-Being

Abstract: Research on choirs and other forms of group singing has been conducted for several decades and there has been a recent focus on the potential health and well-being benefits, particularly in amateur singers. Experimental, quantitative, and qualitative studies show evidence of a range of biopsychosocial and well-being benefits to singers; however, there are many challenges to rigor and replicability. To support the advances of research into group singing, the authors met and discussed theoretical and methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 125 publications
(184 reference statements)
0
53
0
2
Order By: Relevance
“…Introduction A significant body of evidence points to the positive health and wellbeing benefits associated with group singing (Skingley and Bungay 2010;Coulton et al 2015;Fancourt et al 2016;Williams et al 2018;Dingle et al 2019), which have broad appeal to a wide public (Eno 2008;Burkeman 2015). This article contributes to such discussion by further illustrating the importance of representing participants' personal perspectives of group singing (Dingle et al 2019, p. 10) through an analysis of their experiences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction A significant body of evidence points to the positive health and wellbeing benefits associated with group singing (Skingley and Bungay 2010;Coulton et al 2015;Fancourt et al 2016;Williams et al 2018;Dingle et al 2019), which have broad appeal to a wide public (Eno 2008;Burkeman 2015). This article contributes to such discussion by further illustrating the importance of representing participants' personal perspectives of group singing (Dingle et al 2019, p. 10) through an analysis of their experiences.…”
mentioning
confidence: 99%
“…There is a similar growing body of evidence for the individual benefits of group singing in terms of wellbeing Clift et al 2017;Shakespeare and Whieldon 2017;Dingle et al 2019), emotion regulation (Dingle et al 2017) and physical health, particularly in relation to respiratory function and treatment of Parkinson's Disease (BBC Health Check 2018; Kreutz et al 2003Kreutz et al , 2004Skingley et al 2011;Morrison and Clift 2013), again with similar challenges relating to isolating particular effects because of the polyvalent complexity of group singing as an activity.…”
mentioning
confidence: 99%
“…Participation in singing groups presupposes a regular physical and social activity, which requires changes to daily routines, increased physical activity, respiratory activity, mobility and longer periods standing up. Only a few experimental or quasi-experimental studies have provided evidence of measurable health benefits of a singing group activity [ 28 ]. In a quasi-experimental study, following participation in a choir program for 12 months and 24 months (Cohen et al 2006, 2007), the intervention group reported a higher overall rating of physical health, fewer doctor’s visits, less medication use, fewer instances of falls, and fewer other health problems than the comparison group [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously stated, the scientific literature on singing group interventions has demonstrated benefits on the well-being, quality of life, lung function, depression, anxiety, and stress symptoms of older adult participants [ 28 ]. However, literature reviews also highlight the lack of RCTs with blinding of conditions and follow-up collection, and limitations of the studies including biased selection of participants, small sample sizes, and selective reporting of outcomes, resulting in the weak validity of some of the results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation